Convair B-58 Hustler Cold War nuclear bomber - Braas, Nico (Lanasta, 2023)
When the B-58 Hustler bomber entered service in 1958 it was a very futuristic looking delta wing bomber, creating a lot of sensation. Intended as a successor of the B-47 Stratojet it could reach twice the speed of sound. However, problems occurred during the development process and costs risings went so out of control that the whole project was almost cancelled a few times. Strategic Air Command was initially against ordering the B-58 for service, not only because of its complexity but also since they saw no advantage of a Mach 2 bomber over other types. Despite this the B-58 entered service at S.A.C. in 1960. It would have a relatively short operational career.